Code Mixing in Mia Chuz's Wedding Agreement Novel and its Implication for the Learning of Advertising, Slogan and Poster Texts in Junior High School - Kharisma Devi; Albertus Purwaka; Indra Perdana (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The Wedding Agreement novel by Mia Chuz is a form of written literature containing code-mixed language elements. Code mixing is presented in the form of inserting English elements into Indonesian. The purpose of this study was to describe the form of linguistic elements, the causal factors and the function of mixing the English code in the novel Wedding Agreement by Mia Chuz and the implications for learning advertising texts, slogans and posters for class VIII SMP. The approach used in this study is a qualitative approach using content analysis techniques. The results of the study found data containing the form of linguistic elements of English code mixing in the form of inserting elements in the form of words, phrases, basters, and clauses as well as causal factors and functions of English code mixing in Mia Chuz's novel Wedding Agreement. The implications of this research can be applied for the teaching of advertising texts, slogans and posters for class VIII SMP in basic competence 3.4 Examine the presentation patterns and language of advertisement texts, slogans and posters (which make one proud and motivating) from various sources that are read and heard.